Multimeric Amphipathic α‐Helical Sequences for Rapid and Efficient Intracellular Protein Transport at Nanomolar Concentrations. Issue 8 (19th June 2018) - Oh, Jae Hoon; Chong, Seung‐Eun; Nam, Sohee; Hyun, Soonsil; Choi, Sejong; Gye, Hyojun; Jang, Sangmok; Jang, Joomyung; Hwang, Sung Won; Yu, Jaehoon; Lee, Yan
Abstract: An amphipathic leucine (L) and lysine (K)‐rich α‐helical peptide is multimerized based on helix‐loop‐helix structures to maximize the penetrating activities. The multimeric LK‐based cell penetrating peptides (LK‐CPPs) can penetrate cells as protein‐fused forms at 100–1000‐fold lower concentrations than Tat peptide. The enhanced penetrating activity is increased through multimerization by degrees up to the tetramer level. The multimeric LK‐CPPs show rapid cell penetration through macropinocytosis at low nanomolar concentrations, unlike the monomeric LK, which have slower penetrating kinetics at much higher concentrations. The heparan sulfate proteoglycan (HSPG) receptors are highly involved in the rapid internalization of multimeric LK‐CPPs. As a proof of concept of biomedical applications, an adipogenic transcription factor, peroxisome proliferator‐activated receptor gamma 2 (PPAR‐γ 2), is delivered into preadipocytes, and highly enhanced expression of adipogenic genes at nanomolar concentrations is induced. The multimeric CPPs can be a useful platform for the intracellular delivery of bio‐macromolecular reagents that have difficulty with penetration in order to control biological reactions in cells at feasible concentrations for biomedical purposes. Abstract : Multimeric amphipathic α‐helical peptides based on leucine (L) and lysine (K)‐rich sequences facilitate more efficient and faster penetration of active proteins at over 100‐fold lower concentrations than Tat peptide. The multimeric cell penetrating peptides (CPPs) can deliver a master adipogenic transcription factor, peroxisome proliferator‐activated receptor gamma 2 (PPAR‐γ  2), as a fused form to induce adipogenesis at nanomolar concentrations.